Evaluasi sistem akuntansi penjualan kredit pada PT Teratai Kabupaten Sumba Timur - Ana Intan Kahi; Edi Subiyantoro; Fitriana Santi; Hanjar Ikrima Nanda (University of Merdeka Malang, 2021)
In increasing revenue, PT Teratai seeks to increase sales volume. One of the efforts to increase sales is to provide credit sales facilities to customers. Based on the results of observations found several problems including the credit sales accounting system, documents and records on the credit sales system including the eyebrow chart. The credit sales accounting system. This study aims to determine how the credit sales accounting information system of PT Teratai. Data collection techniques in this study using the interview method. The data collected was analyzed descriptively qualitatively. The results of the study show that PT Teratai credit sales system has not been effective. It was found that there was no separation of several functions, namely sales, collection and credit.